2019
DOI: 10.3390/cells8111391
|View full text |Cite
|
Sign up to set email alerts
|

Extrachromosomal Histone H2B Contributes to the Formation of the Abscission Site for Cell Division

Abstract: Histones are constitutive components of nucleosomes and key regulators of chromatin structure. We previously observed that an extrachromosomal histone H2B (ecH2B) localizes at the intercellular bridge (ICB) connecting the two daughter cells during cytokinesis independently of DNA and RNA. Here, we show that ecH2B binds and colocalizes with CHMP4B, a key component of the ESCRT-III machinery responsible for abscission, the final step of cell division. Abscission requires the formation of an abscission site at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 58 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…HIPK2 has been shown to contribute to cytokinesis through two distinct targets, ecH2B, which contributes to the formation of the abscission site ( Monteonofrio et al, 2019 ), and Spastin, which severs microtubules for the final cut ( Pisciottani et al, 2019 ). Thus, we quantify MBRs also after depletion of Spastin and ecH2B obtained by transfecting HeLa cells with Spastin-specific siRNAs (siSpastin) and H2B-specific siRNAs (si-ecH2B), as reported ( Monteonofrio et al, 2019 ; Pisciottani et al, 2019 ). Alongside, for each condition, we also evaluated the induction of cytokinesis defects by analyzing the percentage of aberrant midbodies and binucleated cells, as we previously reported ( Rinaldo et al, 2012 ) ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HIPK2 has been shown to contribute to cytokinesis through two distinct targets, ecH2B, which contributes to the formation of the abscission site ( Monteonofrio et al, 2019 ), and Spastin, which severs microtubules for the final cut ( Pisciottani et al, 2019 ). Thus, we quantify MBRs also after depletion of Spastin and ecH2B obtained by transfecting HeLa cells with Spastin-specific siRNAs (siSpastin) and H2B-specific siRNAs (si-ecH2B), as reported ( Monteonofrio et al, 2019 ; Pisciottani et al, 2019 ). Alongside, for each condition, we also evaluated the induction of cytokinesis defects by analyzing the percentage of aberrant midbodies and binucleated cells, as we previously reported ( Rinaldo et al, 2012 ) ( Supplementary Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In details, cells were transfected with a mix of at least two stealth siRNAs at a final concentration of 40 nM using Lipofectamine RNAi MAX (Life Technologies). Depletion of ecH2B was obtained as in Monteonofrio et al, 2019. Briefly, cells were transfected with a mix of nine siRNAs each at 10 nM in a double pulse, the second one 24 h after the first one.…”
Section: Rna Interference and Expression Vector Transfectionmentioning
confidence: 99%
See 2 more Smart Citations
“…One additional proliferation-associated role of HIPK2 has been reported in abscission, the final step of cytokinesis, in which the two daughter cells are physically separated [41][42][43]. We have shown that HIPK2 localizes at the intercellular bridge (ICB) connecting the daughter cells, in an Aurora B-dependent manner [44] and contributes to abscission by phosphorylating the extrachromosomal histone H2B at S14 [42,45] and the microtubule-severing enzyme spastin at S268 [46]. Loss of HIPK2 results in cytokinesis failure, the accumulation of tetra and polyploid cells, and the generation of aneuploidy, chromosomal instability, and increased tumorigenicity, supporting a caretaker function [47].…”
Section: Introductionmentioning
confidence: 86%